Analysis of the clinical features of Japanese patients with primary ciliary dyskinesia. Issue 2 (April 2022) - Chiyonobu, Kazuki; Xu, Yifei; Feng, Guofei; Saso, Shun; Ogawa, Satoru; Ikejiri, Makoto; Abo, Miki; Kondo, Mitsuko; Gotoh, Shimpei; Kubo, Hisami; Hosoki, Koa; Nagao, Mizuho; et al.
Abstract: Objective: Primary ciliary dyskinesia (PCD) is a rare hereditary disease. Most reports of PCD in Japan are case reports, and clinical analysis has not been performed. Differences in the causative genes might affect the clinical features in different ethnic groups. The purpose of this study was to clarify the clinical features of Japanese patients with PCD. Methods: We performed a retrospective chart review of PCD patients seen at Mie University Hospital and patients whose blood samples were sent to us for genetic analysis from 2011 to 2020. Data on the following items were collected and analyzed: age at first visit to the hospital, age at diagnosis of PCD, process of referral to our facility, chief complaint, situs status, PrImary CiliARy DyskinesiA Rule (PICADAR) score, nasal nitric oxide concentration, otoscopic findings, rhinoscopic findings, and paranasal computed tomography scan findings. Results: Sixty-seven patients (24 male, 43 female) were diagnosed with PCD during the study period. Age at diagnosis ranged from 2 months to 69 years (median, 17 years). Respiratory symptoms (77%) were the most common complaint, followed by nasal (15%) and aural (8%) symptoms. Situs inversus was present in 17 (25%) cases. Only 2 cases had congenital cardiac anomalies. The mean PICADAR score was 7.3 (range, 3–14) points. Approximately 50% of tympanic membranes showed retraction, suggesting otitis media with effusion. The mean Lund-Mackay score was 12.8 (range, 7–17) points, suggesting that the radiographic findings were not always severe. There was no significant difference in the total Lund-Mackay score between patients with and without situs inversus (12.7 vs. 12.6, respectively). Conclusion: Situs inversus was present in 25% of Japanese PCD patients, which is much lower than observed in other countries. This is a result of differences in the major disease-causing genes. The general rule that "situs inversus is observed in approximately 50% of PCD patients" cannot be applied, at least, in Japanese PCD patients.